On the heterogeneity of the economic value of electricity distribution networks: An application to Germany - Marius Stankoweit; Markus Groth; Daniela Jacob (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2017)
The reliability of the electricity grid is of vital significance for the proper functioning of a society and its economy. The aim of this study is to develop a methodology to quantify differences in the electricity distribution grid's economic importance, and investigate limitations from its application to Germany. To this end, the economic value created from electricity consumption is related to the infrastructure installed to generate that economic value. Based on the Value of Lost Load concept, which captures a consumer's willingness to pay for avoided electricity outages, a macroeconomic approach is applied to determine the economic value generated per kWh on the spatial resolution of counties. Each voltage level's grid length is selected as a proxy for the infrastructure installed. Geographic intersections between counties and network operators are exploited to harmonise these data such that both relate to the same reference unit. The results highlight electricity distribution grids of distinct relative economic importance. Especially under consideration of relevant climate risks, the outcomes strengthen the scientific basis for climate services to the energy sector, and can contribute to the design planning of the distribution grid with respect to for example resilience, redundancy, maintenance and retrofitting measures.
Keywords: D61; L94; Q40; Q54; 330; Blackout costs; Climate Risks; Economic assessment; Electircity distribution networks; Energy transition; Supply Security; Value of lost grid; Value of lost load